A Deep Dive into LAPS SJK Cases: A Qualitative Study on Case Types, Resolution Duration, and Party Compliance - Agi Attaubah Hidayat; Amalia Nur Anwari; Lilis Diah Sugiarti; Muhamad Kholid; Naily Aulia Najah (Trunojoyo Madura University, 2025)
This study comprehensively analyzes the effectiveness of the Alternative Dispute Resolution Institution for the Financial Services Sector (LAPS SJK) through a juridical-empirical approach that integrates semi-structured interviews, observation, and document analysis of annual reports from 2022–2024. The findings reveal that the composition of disputes is consistently dominated by the banking sector and fintech lending, with mediation serving as the overwhelmingly dominant settlement mechanism. On the other hand, the institution faces significant challenges, including a high case-rejection rate, primarily due to non-compliance with the Internal Dispute Resolution (IDR) process and indications of fraud. In terms of timeliness, LAPS SJK has demonstrated remarkable efficiency by compressing its Service Level Agreement (SLA)driven by digital transformation and process optimization. The most substantive achievement is reflected in the increase in voluntary compliance with decisions, indicating strengthened legitimacy and trust in the institution. This research provides an original contribution through empirical evidence of the paradox between procedural justice in mediation and the role of arbitration in ensuring legal certainty, as well as a projective analysis of the integration of Artificial Intelligence (AI) in the development of ADR systems in Indonesia.